The concept of feeling in the philosophy of Jean-Jacques Rousseau - زياد كمال مصطفى , أ. م. د. (lark, 2020)
Rousseau's philosophy of feeling requires an deep look at Rousseau the human, Rousseau the educator, in his isolation and social contract, In his waking dreams and confessions, In the pages of his articles between science, art and music, As well as the original disparity between people and languages, and the innate religion. In this paper, we aim to identify the common denominator between these interdependent contradictions knowledge. We follow a comparative analytical method. We are here with the philosophy of a poet whose heart has been solicited to do justice to the music with a romance of free passion, And intellectual class trips full of intuition and sensations, Rather, it is the philosophy of a poet who turned his heart to do music with romance from free emotion, he love nature as a solo traveler to fly in it with his breathtaking imagination and its striking aesthetic descriptions .It is a philosophy introducing a new system of feeling and reason inaugurated by its Copernican revolution in morality, which Kant will later endorse. It is a philosophy that requires that we take the commandment of its owner, We have to survey our heart, And to "read Rousseau until the beauty of his phrases ceases to seduce our feelings". Only then can we examine it carefully and with reason, So did the philosopher of critical idealism , Let us conclude with the result of our reading of the concept of a feeling of transitioning with Rousseau from moral sense to conscience.
Keywords: Keywords : Natuer , Feeling , Art , Moral .